PROFITABILITAS DAN PENGARUHNYA TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Sri Rahayu (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
The purpose of this study is to test and analyze the effect of profitability as measured by Return of Assets (ROA) on disclosure of Islamic Social Reporting (ISR). This type of research is quantitative research. This study uses secondary data financial statements and company annual reports published by the Jakarta Islamic Index (JII) surviving 2015-2017. The sampling technique uses purposive sampling technique. Data analysis was performed using a simple linear regression equation. The results of this study indicate that profitability has no significant effect on disclosure of Islamic Social Reporting on companies. This study can be concluded that companies listed in the Jakarta Islamic Index (JII) are required to have a high awareness in carrying out disclosure of Islamic Social Reporting (ISR) based on sharia principles so that the role of the economic and spiritual aspects of the company is realized.